Estudo de alterações esofágicas, achados sorológicos, aspectos demográficos e uso de medicamentos em pacientes acometidos por esclerose sistêmica - Debora Cerqueira Calderaro (2009)
Systemic sclerosis is a multisystem disease of unknown etiology characterized by functional and structural abnormalities of small blood vessels, and fibrosis of the skin and internal organs. Esophageal involvement affects 50 to 90% of patients and is characterized byabnormal motility and hypotonic lower esophageal sphincter, diagnosed by esophageal manometry. These abnormalities predispose to gastro-esophageal reflux and its complications, erosive esophagitis, erosions, bleeding, stenosis, Barretts esophagus and adenocarcinoma,better evaluated by upper endoscopy. The aim of this study was the evaluation of esophageal manometric and endoscopic abnormalities, and its determinants, in systemic sclerosis patients from Rheumatology Department of Clinics Hospital of Federal University in Minas Gerais,Brazil. They underwent medical records review, clinical interview and esophageal manometry and endoscopy. Manometric abnormalities were graded as follows: the normal cutoff level for lower esophageal sphincter pressure is 14 mmHg. Patients with less than 80% of peristaltic waves propagated were considered to have abnormal peristalsis. Barretts esophagus was diagnosed when endoscopic abnormalities were confirmed by histological findings of intestinal metaplasia. P-values less than 0.05 were considered significant. Twenty eight patients were included: 71% were women, with medium age and disease duration of 46.4 and 12.0 years. Cutaneous diffuse systemic sclerosis occurred in 39% of patients. Dysphagia, pyrosis and regurgitation were present in 71%, 43% and 61% of patients. Manometry revealed esophageal body hypomotility and hypotonic lower esophageal sphincter, respectively, in82% and 39% of patients. Proximal esophagus was normal. One patient presented esophageal achalasia. Four (14%) patients presented erosive esophagitis and one (3.6%), Barretts esophagus. Manometric and endoscopic findings did not correlate, as most of clinical and serological variables evaluated. The high frequency of manometric abnormalities confirmed the frequency of esophageal abnormalities in systemic sclerosis patients. Achalasia has been rarely described in these patients. Treatment with Nifedipine had no influence in manometric findings. Most clinical and serological variables did not correlate with esophagealabnormalities. Esophagitis and hypotonic inferior esophageal sphincter were more frequent in male patients, as previously reported, or in patients taking cimetidine. The association between cimetidine and the increased occurrence of esophagitis may be explained by the factit was used in low doses or because this drug is not efficient for treating these patients and must be confirmed by other studies. Erosive esophagitis was less common than reported internationally, but similar to another Brazilian study. The lack of association between manometric and endoscopic findings probably is due to the little number of patients included. Clinical and serological variables are the same described for other populations. The lack of correlation between them and esophageal abnormalities confirms some other studies findings. The lack of association between Nifedipine use and manometric findings must be evaluated by other studies, as it has therapeutic issues in these patients. Other studies are warranted for the evaluation of the frequency of erosive esophagitis in Brazilian systemic sclerosis patients and, if they confirm its lower occurrence, its determinants shall be searched.